The Performance Of The State Islamic Religious Councils (SIRCs) In Malaysia : Waqf Efficiency And Determinants - Ibrahim, Dahlia (2017)
This thesis looks at the efficiency of thirteen State Islamic Religious Councils (SIRCs) in managing waqf in Malaysia for the period 2007 to 2013. Two stages of analysis are pertinent to the efficiency study of the SIRCs. In the first stage, the measurement of the technical efficiency of the SIRCs uses two basic models of Data Envelopment Analysis (DEA); the Charnes, Cooper and Rhodes (CCR) model and Banker, Charnes and Cooper (BCC) model. For the purpose of measuring the efficiency, this study uses three inputs and two outputs selected based on the intermediation approach.